Orientational versus esthetical urban street morphology parameterization in Space Syntax. Issue 3 (3rd July 2019) - D'Acci, Luca
ABSTRACT: Current topological and geometrical distances in Space Syntax are based on the premise that each change of direction along a path is a mental cost because one loses orientation. This paper proposes to extend the analysis to the case in which esthetic and variety, rather than orientation, are the key elements of street selection. It is widely recognized that most people are attracted to curvy paths rather than straight ones; therefore, when one is not worried about losing orientation in her walk, or when the preferred path is well recognizable even when it requires changes of direction, we should adopt another criterion to weigh distances: morphoahestetic and networkvariety criteria are shown as potential parameterization for Space Syntax distances.